Design of Web-Based Student Attendance Application at MAN 2 Kabupaten Pandeglang - Hafizh Nurfauzan; Muhamad Riyan Maulana (PT. Altaf Publishing Corp, 2024)
In the current era of rapid technological development, the student attendance system at MAN 2 Pandeglang Regency still uses conventional paper-based methods, which are considered less efficient and error-prone. This research aims to design a web-based student attendance application to improve the efficiency and accuracy of the student attendance recording process. The development method used is the Waterfall method, which provides a systematic and sequential approach in software development, starting from the needs analysis stage to implementation and maintenance. This application is designed to facilitate the attendance process, where students can take attendance independently and the results are directly stored in the school database. The implementation of this application shows an increase in efficiency, with attendance time drastically reduced to less than 2 minutes, compared to the previous method which was more time-consuming. In addition, this application also helps reduce the use of paper and improve the accuracy of attendance data. In conclusion, this web-based attendance application makes a positive contribution in supporting more effective and efficient teaching and learning activities at MAN 2 Pandeglang Regency.